Experiences on the Utility and Barriers of Telemedicine in Healthcare Delivery in Kenya - Simon Onsongo; Charles Kamotho; Tobias F. Rinke de Wit; Kinga Lowrie (International Journal of Telemedicine and Applications)
Introduction. Telemedicine is the provision of health services over a distance using information communication technology devices. Telemedicine is emerging as a promising component of healthcare care delivery worldwide, accelerated by the COVID-19 pandemic. This study assessed the factors promoting uptake, barriers, and opportunities for telemedicine among doctors in Kenya. Methodology. A semiquantitative, cross-sectional online survey was conducted among doctors in Kenya. During a month, between February and March 2021, 1,200 doctors were approached by email and WhatsApp, of whom 13% responded. Findings. A total of 157 interviewees participated in the study. The general usage of telemedicine was 50%. Seventy-three percent of doctors reported using a mix of in-person care and telemedicine. Fifty percent reported using telemedicine to support physician-to-physician consultations. Telemedicine had limited utility as a standalone clinical service. The inadequate information communication technology infrastructure was the most reported barrier to telemedicine, followed by a cultural resistance to using technology to deliver healthcare services. Other notable barriers were the high cost of initial setup limited skills among patients, limited skills among doctors, inadequate funding to support telemedicine services, weak legislative/policy framework, and lack of dedicated time for telemedicine services. The COVID-19 pandemic increased the uptake of telemedicine in Kenya. Conclusion. The most extensive use of telemedicine in Kenya supports physician-to-physician consultations. There is limited single use of telemedicine in providing direct clinical services to patients. However, telemedicine is regularly used in combination with in-person clinical services, allowing for continuity of clinical services beyond the physical hospital infrastructure. With the widespread adoption of digital technologies in Kenya, especially mobile telephone technologies, the growth opportunities for telemedicine services are immense. Numerous mobile applications will improve access capabilities for both service providers and users and bridge the gaps in care.